Climate change and adverse health events: community perceptions from the Tanahu district of Nepal. (2nd March 2015) - Mishra, Shiva Raj; Bhandari, Parash Mani; Issa, Rita; Neupane, Dinesh; Gurung, Swadesh; Khanal, Vishnu
Abstract: Nepal is a country economically dependent on climate-sensitive industries. It is highly vulnerable to the environmental, social, economic and health impacts of climate change. The objective of this study is to explore community perceptions of climate variability and human health risks. In this letter, we present a cross sectional study conducted between August 2013 and July 2014 in the Tanahu district of Nepal. Our analysis is based on 258 face-to-face interviews with household heads utilizing structured questionnaires. Over half of the respondents (54.7%) had perceived a change in climate, 53.9% had perceived an increase in temperature in the summer and 49.2% had perceived an increase in rainfall during the rainy season. Half of the respondents perceived an increase in the number of diseases during the summer, 46.5% perceived an increase during the rainy season and 48.8% during winter. Only 8.9% of the respondents felt that the government was doing enough to prevent climate change and its impact on their community. Belonging to the Janajati (indigenous) ethnic group, living in a pakki, super- pakki house and belonging to poor or mid-level income were related to higher odds of perceiving climate variability. Illiterates were less likely to perceive climate variability. Respondents living in a pakki house, super- pakki, or those who were poor were more likely to perceive health risks. Illiterates were less likely to perceive health risks.